Cooperative Learning Model Jigsaw and Interest Type in Improving Learning Outcomes of SMA Negeri 1 Sutera Kabupaten Pesisir Selatan - Resnawati Resnawati; Siti Fatimah; Buchari Nurdin (Jurnal Aplikasi IPTEK Indonesia, 2019)
Effect of Cooperative Model of Jigsaw Type Learning and Student Interest in improving learning outcomes in SMA Negeri 1 Sutera. The research method used in writing this essay in accordance with the type of research is quasi experimental research (quasi experimental), where the research variables can not be fully controlled. This research has a control group. The research design used to measure learning method and student's interest  toward  the result  of  dissemination  of culture and  religion.  This  research  is parenting at level (2x2), with state of student interest level. The results of the study revealed  (1)  the  learning  outcomes  of  students  who  were  taught  by  the  Jigsaw cooperative  model  approach  were  better  than  the  conventional  approach,  (2)  the students' learning outcomes had high interests taught by the Jigsaw type cooperative model better than the conventional approach, (3) learning of students with low interests taught by Jigsaw type cooperative models is better than conventional models